Teachers' perceptions of the impact of stuttering on the daily life of their students who stutter - Rocha, Mónica S. (2022)
Stuttering is a neurodevelopmental disorder involving interruptions in the flow of speech. The reactions of listeners and others in a child's environment could affect how children perceive their stuttering. Children experience many of their everyday social situations in the school context. Because it might be hard for children who stutter to deal with communication in the school setting, it is essential to know how teachers perceive the impact of stuttering on their students. In this study, we collected data about teachers' perceptions of the impact of stuttering on Portuguese children who stutter using an adaptation of the European Portuguese translation of Overall Assessment of the Speaker's Experience of Stuttering (OASES-S-PT). Participants were 27 teachers and their students who stutter (n=27; mean age=9.0 mos., SD=1.8 mos.), recruited from different cities in Portugal. In general, teachers perceived the overall impact of stuttering in their students' lives as mild-to-moderate. Our results did not reveal any statistically significant differences between the teachers' perceptions of the impact of stuttering and the students' self-reports. Still, there was no statistically significant correlation between the students' impact scores and the teachers' impact scores. Teachers were unable to rate several items on the instrument, which indicates that they were unfamiliar with some aspects of the children's experiences with stuttering. This finding highlights the need to integrate teachers into therapy programs to increase support within the environment of for children who stutter.